Early Speech Intervention in Students with Developmental Language Disorder (DLD) - Axpe-Caballero, María Ángeles; Delgado-Cruz, Atteneri; Acosta-Rodríguez, Victor (Revista Chilena de Fonoaudiología, 2024)
Some children with Developmental Language Disorder (DLD) may experience disruptions in their phonological system, leading to difficulties in speech production. These difficulties appear as substitution errors, syllable structure issues, and distortions, resulting in a higher number of phonological processes (PP) than expected for their age. The main bjective of this study was to design and implement an intervention program based on the principles of stimulability and psycholinguistic approaches to improve speech production in children with DLD. An intervention program was carried out with 24 five-year- old students diagnosed with DLD using the Clinical Evaluation of Language Fundamentals, Spanish Fourth Edition (CELF- 4). Phonological productions were assessed through Registro Fonológico Inducido (RFI). The intervention was structured under a Multi-Tiered System of Supports (MTSS), comprising a total of 30 intervention sessions, each lasting 15 minutes. The activities were designed according to the criteria of gestural support for phonemes and metaphonology. The results reveal a significant reduction in phonological processes following the intervention, particularly in those affecting words and syllables. Based on these findings, we conclude that an intervention combining these approaches effectively reduces PPs. Future research should explore the impact of increasing the length of each session and the number of trials for each goal, as suggested by the literature.